Staphylococcus aureus mastitis: Influence on Milk Composition and Susceptibility to Antibiotics - Mohammed, Rasha T. A.; El Zubeir, Ibtisam, E. M. (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was conducted with the aim of investigating the occurrence of Staphlococcus aureus mastitis in dairy farms in Khartoum State and the chemical composition of S. aureus mastitis milk. Bacteriological analysis and chemical composition was determined with milk analyser Lactoscan. Sixty mastitic milk samples were collected, from which 22 samples were S. aureus. Antimicrobial sensitivity tests, using 8 different antibiotics, were performed against the isolates. About 91% of the isolates were sensitive to chloramphenicol and gentamicin, 86.4% to ciprofloxacin, 77.3% to penicillin G, 64% to augmentin and 63.6% to vancomycin. However, 59% of isolates were resistant to fusidic acid and 54.5% to erythromycin. Chemical analysis of mastitic milk Revealed that the mean value of fat, protein, lactose and solids non fat were 3.00±1.4%, (range 1.6%- 4.1%), 3.6±0.4%, (range 2.9%- 4.3%), 4.8±0.8%, (range 3.8%- 5.6%) and 9.1±0.9% (range 7.5%- 10.5%), respectively. It is concluded that mastitis caused by S. aureus might decrease of the nutritive value of milk through reducing its chemical constituent level. Therefore, applying proper mastitis treatment and control measurement is highly recommended.